Development of Indonesia Halal Agroindustry Global Market in ASEAN: Strategic Assesment - Fajar Surya Ari Anggara (Al Tijarah, 2017)
With the opening of AEC at the end of 2015, ASEAN became one of the largest markets in the world with a population of 633 million. Agroindustry is one of the most important sectors in ASEAN for Global Halal Market. Therefore, Indonesia needs to identify other segments or industries that can re-energize halal agroindustry of the country. This paper discusses the overlooked halal food segment in Indonesia as a catalyst in developing other potential sectors, in line with rapid globalization and internationalization. Using content analysis from various literatures, this exploratory study focuses on the past and current situation of halal food segment, and how its development can potentially affect growing sectors such as tourism and education in Indonesia. A SWOT analysis was conducted to summarize the country’s internal (strengths and weaknesses) and external (opportunities and threats) issues in branding itself.